Scientific reasoning skills and patterns of use of Information and Communication Technologies. The case of the students of the Universidad de Santander (Valledupar, Colombia) (2019)
This research establishes the relationship that has had the development of the skills of scientific reasoning and the patterns of use of tools and resources of information and communication technology (ICT). For that, it is necessary to use Lawson Test and to have into account ICT National Standards for students that USA International Society for Technology in Education (ISTE) suggest. Also, this paper is tackled from a non-experimental design featuring a correlational – transectional range. The population consists of 2035 students from a higher education institution of the Colombian Caribbean coast. Besides, stratified random sampling is used defining, defining strata and a representative sample for academic programs. Personal survey was used to collect information. The existence of relationship between scientific reasoning skills and patterns of use of information and communication technology was confirmed.